What happens between the roça and the urban periphery? Some questions about movement - Benites,Luiz Felipe Rocha (2018)
Abstract This article explores the idea of movement through an analysis of the flows between rural and urban areas, more specifically between small farms (roças) and the peripheries of big cities. I turn to my own ethnographic research on rural and riverside communities in the north of Minas Gerais, as well as ethnographies produced on populations in the Cerrado Mineiro, in order to question the primacy of movement in the definitions of the city and to extend the notion through an approach that incorporates the relations between persons and things circulating in both these social spaces.